Beyond Technical Fixes: climate solutions and the great derangement. (20th April 2020) - Nightingale, Andrea Joslyn; Eriksen, Siri; Taylor, Marcus; Forsyth, Timothy; Pelling, Mark; Newsham, Andrew; Boyd, Emily; Brown, Katrina; Harvey, Blane; Jones, Lindsey; Bezner Kerr, Rachel; Mehta, Lyla; et al.
ABSTRACT: Climate change research is at an impasse. The transformation of economies and everyday practices is more urgent, and yet appears ever more daunting as attempts at behaviour change, regulations, and global agreements confront material and social-political infrastructures that support the status quo. Effective action requires new ways of conceptualizing society, climate and environment and yet current research struggles to break free of established categories. In response, this contribution revisits important insights from the social sciences and humanities on the co-production of political economies, cultures, societies and biophysical relations and shows the possibilities for ontological pluralism to open up for new imaginations. Its intention is to help generate a different framing of socionatural change that goes beyond the current science-policy-behavioural change pathway. It puts forward several moments of inadvertent concealment in contemporary debates that stem directly from the way issues are framed and imagined in contemporary discourses. By placing values, normative commitments, and experiential and plural ways of knowing from around the world at the centre of climate knowledge, we confront climate change with contested politics and the everyday foundations of action rather than just data.